2015
DOI: 10.1016/j.medici.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional (ischemic) mitral regurgitation in acute phase of myocardial infarction: Associated clinical factors and in-hospital outcomes

Abstract: Moderate and severe MR in acute MI is related to age, atrial fibrillation, increased left ventricular diastolic dimensions and decreased ejection fraction. Moderate and severe, but not mild MR is an important clinical contributor to in-hospital cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…It is reported that moderate and severe MR in acute MI is related to increased left ventricular diastolic dimensions. 8 Fazlinezhad and colleagues 10 reported higher grade of diastolic dysfunction, end-diastolic LV pressure in IMR cases. They also had higher Systolic Pulmonary Artery Pressure (SPAP) which was related directly to the severity of MR. MacHaalany et al 9 also showed higher prevalence of PAP, LVESD and LA size in moderate to severe IMR.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is reported that moderate and severe MR in acute MI is related to increased left ventricular diastolic dimensions. 8 Fazlinezhad and colleagues 10 reported higher grade of diastolic dysfunction, end-diastolic LV pressure in IMR cases. They also had higher Systolic Pulmonary Artery Pressure (SPAP) which was related directly to the severity of MR. MacHaalany et al 9 also showed higher prevalence of PAP, LVESD and LA size in moderate to severe IMR.…”
Section: Discussionmentioning
confidence: 94%
“…We observed that cases with IMR are more female, older and smoker. In the literature, cases with moderate to severe IMR were older, 8 with female dominance. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Patients at risk are elder, more likely to be female, to have lower EF and multi-vessel CAD, these findings are well acknowledged in previous reports. [18][19][20] Many factors contribute to the occurrence of IMR, including postinfarct LV remodeling, papillary muscle displacement, contractile dysfunction of the left ventricle, structural changes of the valvular ring, and ventricular electro-mechanical dys-synchrony. 5,6 Of these factors, left ventricular remodeling is thought to be the most important mechanism responsible for IMR.…”
Section: Discussionmentioning
confidence: 99%
“…Mean platelet volume, which reflects the platelet production and function, is associated with MR severity and thromboembolism risk[49, 50]. In terms of electrocardiographic markers, reduced LVEF, increased left atrial dimensions and left ventricular end diastolic diameter have been found to predict MR severity, which is associated with increased in-hospital cardiac death risk and overall mortality[47, 51, 52]. P wave indices reflective of left atrial remodeling, such as P wave area and P wave terminal force, was predictive of MR severity[11, 12].…”
Section: Discussionmentioning
confidence: 99%